Collection, evaluation and phenotypic diversity assessment of maize (Zea mays) germplasm from North Eastern Himalayan region - KUMARI, JYOTI; KUMAR, ASHOK; SINGH, T P; BHATT, K C; MISHRA, A K; SEMWAL, D P; SHARMA, R K; RANA, J C (The Indian Journal of Agricultural Sciences, 2017)
Primitive landraces and traditional cultivars of maize (Zea mays L.) are invaluable resources for the humankind. These need to be collected, evaluated, conserved and utilized for increasing agricultural production and quality enhancement. Based on extensive survey, 75 diverse maize accessions were collected from Nagaland and Manipur states of the North Eastern Himalayan region. These collections were evaluated under two different agro-ecological regions, New Delhi and Shillong during kharif 2012 and 2013 using 12 quantitative variables. There was significant morphological variability among the accessions. Trait specific cultivars were identified based on exploration related knowledge and phenotypic valuation. The cluster analysis was performed to assess the variation among genotypes and grouped them into five clusters based on phenotypic traits. The principal component analysis (PCA) was subjected to quantitative datasets to group the accessions and to study contribution of traits for phenotypic variation. The first two principal components explained more than 50% of the phenotypic variation. Plant height, ear height, grain yield, ear width, number of kernel rows and number of kernels per row were major contributing traits towards phenotypic diversity. The different groups obtained can be useful for deriving the inbred lines with diverse features and diversifying the heterotic pools.